2009
DOI: 10.1016/j.physletb.2009.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Five-dimensional black hole string backgrounds and brane universe acceleration

Abstract: We examine background solutions of black hole type arising from the string effective action in five dimensions. We derive the unique metric -dilaton vacuum which is a Schwarzschild type black hole. It is found that it can be extended to incorporate electric charge without changing the topology of the three space. Kalb-Ramond charge may also be introduced if the three space is closed. The basic features of the cosmology induced on a three brane evolving in this background are also discussed. 1

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…In this paper, therefore, we will consider the five dimensional Kalb-Ramond (KR) theory [79][80][81][82]. It is known that an effective action with a scalar-Kalb-Ramond interaction is equivalent to an effective action with a scalarvector interaction in five dimensional (5D) spacetime [83][84][85][86]. Therefore the 5D KR model is a 5D extension of the KSW model.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, therefore, we will consider the five dimensional Kalb-Ramond (KR) theory [79][80][81][82]. It is known that an effective action with a scalar-Kalb-Ramond interaction is equivalent to an effective action with a scalarvector interaction in five dimensional (5D) spacetime [83][84][85][86]. Therefore the 5D KR model is a 5D extension of the KSW model.…”
Section: Introductionmentioning
confidence: 99%
“…In this work we examine the cosmology induced on a brane moving in the five-dimensional Schwarzschild stringy black hole background found in [46], paying attention mainly in the acceleration parameter and insisting in deriving the today value of the acceleration to follow a decelerating phase. Indeed we found that introducing on the brane matter with the characteristics of quintessence or phantom even in the simple case we have considered with constant w e and no coupling of the brane matter to the dilaton field, acceptable behavior of the acceleration parameter can be achieved.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In this section we briefly review the derivation of the static five-dimensional background found in [46] which will be used for the cosmological study. The bosonic part of the low energy limit of the string effective action is…”
Section: Five-dimensional String Effective Action Backgroundmentioning
confidence: 99%
See 2 more Smart Citations